The relationship between extreme contexts, organizational change capacity, and firm product and process innovation - Akgun, Ali E. E.; Cemberci, Murat; Kircovali, Selim (EMERALD GROUP PUBLISHING LTD, 2023)
PurposeThis study investigates the mediating role of organizational change capacity (OCC) in the relationship between the perception of extreme contexts and firm product and process innovation, which was not empirically investigated in the literature. In addition, this study explores the moderating role of the perception of extreme contexts-related variables, which were not operationalized in ordinary firms, on the relationship between OCC and firm product and process innovation.Design/methodology/approachA questionnaire-based research was conducted to test the suggested hypotheses. The data were gathered from 90 firms during the peak period of COVID-19.FindingsThis study shows that OCC, which covers contexts, process and learning dimensions, fully mediates the relationship between the perception of extreme contexts and firm product and process innovation. Also, this study discovers that the perception of extreme contexts, including temporal ordering of extremity, the magnitude of consequences, proximity among people and operational deficiencies, positively moderate the relationship between OCC and firm product innovation.Research limitations/implicationsThis study has constraints inherited in survey design, primarily sampling and country context.Originality/valueThis study identifies, conceptualizes and operationalizes the term extreme context, conceptually argued for particular organizations/units in ordinary/mundane organization settings so far. In addition, this study extends the current understanding of how the perception of extreme contexts interacts with a firm's capability to increase innovation efforts. Further, this study shows how OCC mediates the relationship between extreme contexts and firm product and process innovation.
Keywords: Organizational change capacity; Extreme contexts; Product innovation; Process innovation; DYNAMIC CAPABILITIES; BLACK-BOX; CRISIS; PERFORMANCE; SENSEMAKING; MANAGEMENT; LEADERSHIP; SERVICE; ORIENTATION; RESILIENCE; Business & Economics